PENGARUH BAHASA IBU TERHADAP PERKEMBANGAN BAHASA INDONESIA ANAK DI TK AZKIA KEPENGHULUAN SUNGAI PINANG KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR - Hasan Hasan; Novita Sari; Delima Putri (Jurnal Syaikh Mudo Madlawan: Kajian Ilmu-Ilmu Keislaman, 2026)
Language is inseparable from the history of human life. This is because language serves as a means of communication between people. Without language, humans would be unable to communicate and interact. Since language is so important, we have a duty to teach it to our children—particularly their mother tongue or the everyday language used for communication within the family. The research question in this study is: To what extent does the mother tongue influence the development of Indonesian language skills among children at Azkia Kindergarten in the village of Sungai Pinang, Kubu Babussalam Subdistrict, Rokan Hilir Regency? This study aims to demonstrate the extent of the mother tongue’s influence on children’s language development at Azkia Kindergarten in the village of Sungai Pinang, Kubu Babussalam Subdistrict, Rokan Hilir Regency. This study is a field assessment. The subjects of this study are all 17 students at Azkia Kindergarten. The results of this study are as follows: 2 students (11.76%) have very good language development. 6 students (35.29%) have good language development. A total of 9 children (52.94%) had adequate language development.